Effect of Types of Family on Learner Drug Abuse in Selected High Schools in Soweto, South Africa - Mnyamana, Nzukiso; Aloka, Peter JO (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2026)
This study examined the effect of the types of family on learner drug abuse in selected high schools in Soweto, South Africa. The study adopted a correlational survey research design. The sample size comprised 80 students obtained using census sampling. Data from the learners was gathered using the learner drug abuse and family drug abuse scales. Data was analyzed using inferential statistics such as Analysis of Variance (ANOVA) and Tukey HSD test. The study findings established that the type of family has statistically significant relationship with (F=3.972; P=.011) the level of drug abuse among the secondary school learners, with learners living in well-organized type of family, like nuclear, are likely to indulge less in drug abuse than their counterparts who live in a single-parent family, child headed family, and extended family. The study recommends that school counsellors should adopt holistic therapy techniques to support learners who abuse drugs.